STUDY ON GRAPHENE GROWTH AT LOW TEMPERATURE BY METHOD OF HOT WIRE CELL IN PLASMA VERY HIGH FREQUENCY PECVD FOR AMORPHOUS/MICROCRYSTAL SILICON SOLAR CELLS APPLICATION - Momang Yusuf, A
The increasing demand for energy in the future has encouraged efforts to find sources of electrical energy other than the energy sources that have been used so far. One source of energy that is abundantly available and has the potential to be utilized is solar energy. For this purpose, a solar cell is needed to convert the solar energy into electrical energy. Currently, thin film amorphous silicon is one of the materials that is used to fabricate low-cost solar cell. However, the efficiency of amorphous silicon basedsolar cells is still low compared to crystalline silicon solar cell. In addition, amorphous silicon solar cells indicate poor stability due to a decrease in efficiency after being exposed to sunlight for a long time, a phenomenon known as StablerWronski effect. Therefore, various efforts are still being researched to increase the efficiency as well as the stability of the amorphous silicon-based solar cells. One of the efforts that is currently attracting attention is the application of carbonbased materials, especially graphene, in the layer structure of the device. Various research has revealed that graphene has several characteristics that potentially to be applied to solar cells, including high transparency and conductivity. In fact, graphene has been used as transparent electrode layer as well as active layer in solar cell devices. However, fabrication cost of these devices was still relatively high due to the high temperature requirement for graphene growth and the use of crystalline silicon for solar cell fabrication which also requires high temperature. In addition, the fabrication method requires transferring graphene from its synthesis substrate to the substrate that will be used as the device substrate. This transfer process requires additional costs, is difficult and time-consuming process, thus it is considered less economical and impractical. As an effort to overcome these obstacles, in this research,study on graphene growth at low temperature was carried out using method of Hot Wire Cell in Plasma Very High Frequency Plasma Enhanced Chemical Vapor Deposition Method (HWC IP VHF PECVD). The obtained graphene was applied in amorphous/microcrystallinebased solar cell structured: corning glass/TCO/Ni/graphene/i-?c-Si:H/n-a-Si:H. The graphene produced in this study has quite small averagely crystal-size which is in order of magnitude of nanometers or is referred to as nanocrystalline graphene. The growth of this nanocrystalline graphene was carried out at a relatively low temperature of 300 ?C at a chamber pressure of 500 mTorr, plasma generating power between 8 watts – 12 watts, for 10 minutes with the aid of nickel catalyst. Whereas the microcrystalline silicon layers for solar cell device fabrication were grown at temperature of 275 ?C. As an initial application, performance of the fabricated solar cell result in an opencircuit voltage of 0.68 V, short-circuit current density of 0.03 mA, fill factor of 0.38, and efficiency of 0.07%. This result is better than the previously made graphene/hydrogenated amorphous silicon based solar cell device which only produced an efficiency of 0.00167%, with an open circuit voltage value of 0.15 V, a short circuit current density of 0.0748 mA/cm2 , and a fill factor of 0.2. Compared to other studies that have applied graphene as a transparent electrode layer on a crystalline silicon substrate, this research is the first one to apply graphene as an alternative for type-p thin film silicon in an amorphous/ microcrystalline silicon p-i-n solar cell. In addition, the device fabrication in this study was conducted ‘in-situ’, starting from deposition of graphene on a corning glass/TCO substrate that has been coated with a thin layer of nickel as a catalyst, deposition an intrinsic microcrystalline thin film silicon on the graphene, and finally deposition of n-type amorphous thin film silicon on the intrinsic microcrystalline thin film silicon. The ‘in-situ’ fabrication in this method has abolished graphene transfer process thus it is considered as more economical and practical method. The initial result achieved by this study is expected to pave the way for efforts to increase the efficiency and stability of amorphous/microcrystalline silicon-based solar cell device which are well-known to be inexpensive, especially by integrating new two-dimensional materials such as graphene and its derivatives into its structure.